Identification of most tolerant lichen species to vehicular traffic’s pollutants: a case study at Batu Pahat - Muhammad, Norhayati; Hashim, Nor Haslina; Khairuddin, Nur Ain; Yusof, Hasliza; Jusoh, Samsiah; Abas, Azlan; A. Talip, Balkis; Abdullah, Norazlin; Din, Laily (Penerbit Akademia Baru, 2018)
Bio-indicators are organisms that can be used for the identification and qualitative determination of human generated environmental factors. The decreasing population of sensitive lichens in specific regions around the world due to low air quality level has make lichens as a bio-indicator for air pollution. Lichen is a result of symbiotic association of fungus and alga and well known for having wide variety of sensitivity towards environmental stressors such as air quality and climate change. This study aims to identify the most tolerant lichen species to vehicular traffic’s pollutant at Batu Pahat urban and suburban areas by using Index of Atmospheric Purity (IAP) method. The color spot test, thin layer chromatography (TLC) profiling and morphological analysis were employed for species identification. The results have shown that Dirinaria picta has been identified as the most tolerant lichen against pollutants from vehicle traffic. The results also indicated that the air quality of Batu Pahat town/urban area could be considered as moderately clean.